Promotion of first internode elongation in perennial paddy weeds Sagittaria trifolia and Sagittaria pygmaea tubers by oxygen depletion and carbon dioxide. Issue 4 (December 2016) - Sasayama, Daisuke; Ikemachi, Kenta; Sakai, Hisateru; Fukayama, Hiroshi; Itoh, Kazuyuki; Azuma, Tetsushi
Abstract : The semiaquatic plants, S agittaria trifolia and S agittaria pygmaea, are perennial and troublesome weeds of rice paddy fields. These species mainly reproduce vegetatively via tubers, which sprout after the rice paddy fields are irrigated. Sprouting finally leads to the emergence of the shoots from the water in the paddy fields. In both species, the first internode elongates around the time of emergence and this lifts the shoot meristems in the soil, aiding in the establishment of the young plants. Therefore, elongation of the internode is a factor that determines the weed damage to rice caused by these species. In this study, the first internode elongation of both species was characterized. During emergence, S . trifolia and S . pygmaea showed distinct growth patterns. In S . trifolia, the internodes elongated before the emergence of the shoots from the water; whereas, in S . pygmaea, the internodes started to elongate only after emergence. We examined environmental prerequisites for internode elongation, and found that the internode elongation of S . trifolia was induced by submergence and was independent of the soil cover, while that of S . pygmaea required both submergence and covering. Next, we determined which gaseous factors were responsible for internode elongation. Treatment with ethylene, which enhances growth of several other aquatic and semiaquatic plants, did not stimulate internode elongation in either species under an anaerobic condition. Our results suggested that the gaseous factor stimulating internode elongation in S . trifolia and S . pygmaea may be oxygen depletion and carbon dioxide, respectively.